Monetary policy expectations and the Malaysian deposit market: analysis of Islamic rates of return and conventional interest rates. (2017) - Ito, Takayasu
This paper focuses on the impact of monetary policy expectations on deposit rates in Malaysia. Comparative analyses of Islamic rates of return and conventional interest rates are conducted. Bank Negara Malaysia has been successful to some extent in communicating with financial markets because monetary policy expectations have some impact on Islamic rates of return or conventional interest rates up to the maturity of 12 months. Islamic rates of return and conventional interest rates shape the short-term deposit market in Malaysia, and they are driven by monetary policy expectations. Islamic finance is not different from conventional finance in terms of the formation of deposit rates. Bank Negara Malaysia plays an important role in the formation of Islamic rates of return and conventional interest rates in the deposit market up to 12 months.